Surgical Repair of Triangular Fibrocartilage Complex Tears: A Systematic Review - Liu, Edward H.; Suen, Kary; Tham, Stephen K.; Ek, Eugene T. (Journal of Wrist Surgery, 2020)
Objective This study systematically reviews the outcomes of surgical repair of triangular fibrocartilage complex (TFCC) tears. Existing surgical techniques include capsular sutures, suture anchors, and transosseous sutures. However, there is still no consensus as to which is the most reliable method for ulnar-sided peripheral and foveal TFCC tears.Methods A systematic review of MEDLINE and EMBASE was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The focus was on traumatic Palmer 1B ulna-sided tears. Twenty-seven studies were included, including three comparative cohort studies.Results There was improvement in all functional outcome measures after repair of TFCC tears. The outcomes following peripheral and foveal repairs were good overall: Mayo Modified Wrist Evaluation (MMWE) score of 80.1 and 85.1, Disabilities of the Arm, Shoulder and Hand (DASH) score of 15.7 and 15.8, grip strength of 80.3 and 92.7% (of the nonoperated hand), and pain intensity score of 2.1 and 1.7, respectively. For peripheral tears, transosseous suture technique achieved better outcomes compared with capsular sutures in terms of grip strength, pain, Patient-Rated Wrist Evaluation (PRWE), and DASH scores (grip 85.8 vs. 77.7%; pain 1.5 vs. 2.2; PRWE 11.6 vs. 15.8; DASH 14.4 vs. 16.1). For foveal tears, transosseous sutures achieved overall better functional outcomes compared with suture anchors (MMWE 85.4 vs. 84.9, DASH 10.9 vs. 20.6, pain score 1.3 vs. 2.1), but did report slightly lower grip strength than the group with suture anchors (90.2 vs. 96.2%). Arthroscopic techniques achieved overall better outcomes compared with open repair technique.Conclusion Current evidence demonstrates that TFCC repair achieves good clinical outcomes, with low complication rates.Level of Evidence This is a Level IV, therapeutic study.
Keywords: triangular fibrocartilage; TFCC; repair; foveal; peripheral tear; systematic review